2007
DOI: 10.1196/annals.1398.018
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Step Mechanism of Virus‐induced Autoimmune Hemolytic Anemia

Abstract: Viruses are associated with the development of autoantibody-mediated blood autoimmune diseases. A two-step mechanism could explain virus involvement in the development of experimental hemolytic anemia. Immunization of normal mice with rat erythrocytes results in an autoantibody production that could be enhanced by viral infection, without erythrocyte destruction. Inoculation of the same virus when autoantibodies are at high levels triggers clinical anemia. This results from macrophage activation by gamma-inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…[4][5][6] However, in the primary form of AIHA, no inciting cause is identified. 7 The basic pathogenesis of primary AIHA is poorly understood, but clearly results from a failure of tolerance mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] However, in the primary form of AIHA, no inciting cause is identified. 7 The basic pathogenesis of primary AIHA is poorly understood, but clearly results from a failure of tolerance mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Strong evidence has been reported that LDV exacerbates diseases, such as thrombocytopenia and hemolytic anemia by increasing the uptake of target cells by macrophages [1][2][3][4]. Although platelets or erythrocytes are most often ingested after opsonization with IgG autoantibodies, LDV infection alone may also result in antibody-independent thrombocytopenia [15].…”
Section: Discussionmentioning
confidence: 99%
“…Mouse infection with the lactate dehydrogenase-elevating virus (LDV) has been shown to exacerbate autoimmune diseases, such as antibody-mediated anemia [1,2] and thrombocytopenia [3,4]. This effect of LDV infection can be explained by the enhanced phagocytic activity of macrophages [1,3], thus leading to the engulfment and destruction of opsonized cells in response to the macrophage activation, which is mostly triggered by the gammainterferon (IFN-γ) secreted by natural killer cells upon infection [5].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, antiviral prophylaxis is stopped 6 months post‐LT in our protocol, coinciding with the cases of late IHA, and further putting into question the role of CMV prophylaxis as opposed to pre‐emptive strategies . Although the pathophysiology of IHA is beyond the scope of the present study, genetic diversity of the immune response both to viral triggers and to immunosuppression may act as a cofactor …”
Section: Discussionmentioning
confidence: 99%